2020
DOI: 10.1002/stem.3263
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular consequences of fusion genes in myeloid malignancies

Abstract: Leukemias are heterogeneous diseases characterized by aberrant hematopoietic stem and progenitor cells (HSPCs). Oncogenic fusion genes and proteins, produced via gross chromosomal rearrangements, such as chromosomal translocation, insertion, and inversion, play important roles in hematologic malignancies. These oncoproteins alter fundamental cellular properties, such as self‐renewal, differentiation, and proliferation, and confer leukemogenic potential to HSPCs. In addition to providing fundamental insights in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Cloning translocation breakpoints have given important insights into the pathogenesis of this disorder. Mutations in transcription factor genes involved in normal hematopoietic production are among the chromosomal aberrations seen in acute myeloid leukemia [ 4 ]. Mutations affecting transcription factors and key cell genes result in uncontrolled proliferation and compromised differentiation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cloning translocation breakpoints have given important insights into the pathogenesis of this disorder. Mutations in transcription factor genes involved in normal hematopoietic production are among the chromosomal aberrations seen in acute myeloid leukemia [ 4 ]. Mutations affecting transcription factors and key cell genes result in uncontrolled proliferation and compromised differentiation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effects unique to SVs are gene fusions, gene deletions, gene duplications, and genome rearrangements. Gene fusions are cases where a SV causes parts of two genes to end up back-to-back, resulting in the formation of a hybrid gene which may alter considerably fundamental cellular processes, such as proliferation, self-renewal, and differentiation of the cell, which properties are playing key roles in cancer [19]. The deletion or duplication of genes or their regulatory elements can have a large impact on the production of RNA and, in turn, that of the final protein products.…”
Section: Structural Variantsmentioning
confidence: 99%
“…And the majority of AML events are correlative with abnormal chromosomal translocations, which generates the oncogenic fusion genes. Mounting studies have demonstrated the central roles of fusion genes in initiating the leukemogenesis (4)(5)(6). And the successful strategies are paralleled by the decrease or degradation of chimeric proteins (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…AML is frequently associated with chromatin rearrangement, including translocation and inversion, which generate oncogenic fusion proteins, among of which four most common chimeric proteins should be paid more attention, including AML1-ETO, PML-RARa, CBFb-MYH11, and MLL-MLLT3 (4,6,(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation